THE EFFECT OF INVESTMENT, CONSUMPTION, AND GOVERNMENT SPENDING ON POVERTY THROUGH ECONOMIC GROWTH - Siti Aisah; Dita Rosyalita; Danil Surasa; Abdul Aziz; Syaeful Bakhri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the influence of consumption, investment, government spending, and poverty on economic growth during the 2014 Q1–2024 Q4 period. The study uses a quantitative approach with secondary data in the form of time series obtained from official sources. The collected data were tested using multiple linear regression, and supported by descriptive statistical tests, stationarity tests, correlation tests, and autocorrelation tests. The results show that consumption, investment, and government spending have a positive but insignificant influence on economic growth. Conversely, poverty has a negative but significant influence on economic growth. Simultaneously, all independent variables do not have a significant effect on economic growth. The relatively low coefficient of determination value indicates that there are still other factors outside the model that influence economic growth. This finding emphasizes the importance of poverty reduction in driving increased economic growth.